2016
DOI: 10.1017/s0030605316000740
|View full text |Cite
|
Sign up to set email alerts
|

The Vulnerable giant anteaterMyrmecophaga tridactyla: new records from the Atlantic Forest highlands and an overview of its occurrence in protected areas in Brazil

Abstract: The giant anteater Myrmecophaga tridactyla is categorized as Vulnerable on the IUCN Red List, and is extinct in several locations as a result of environmental pressures. We present the first records of the giant anteater in the largest continuous expanse of the Atlantic Forest biome, in southern Brazil, highlighting its occurrence in the highlands of the Serra do Mar mountain range. During a camera-trapping survey of medium and large mammals we obtained two records of the species, one in 2013 and the other in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Both species were usually detected alone, but occasionally females were observed carrying pups on their back, as reported by Desbiez & Medri (2010), Figel et al (2015) and Passos et al (2016). Anteaters are usually nocturnal, although they occasionally engage in diurnal activity (Rodrigues et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both species were usually detected alone, but occasionally females were observed carrying pups on their back, as reported by Desbiez & Medri (2010), Figel et al (2015) and Passos et al (2016). Anteaters are usually nocturnal, although they occasionally engage in diurnal activity (Rodrigues et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Although giant anteater studies can be found in Brazil (Miretzki & Goss Braga, 2014;Passos et al, 2016;Mamalis et al, 2018) and the North of Argentina (Perez Jimeno & Llarin Amaya, 2009;Quiroga et al, 2016), data of these species in Paraguay is still scarce or even absent (De La Sancha et al, 2017;Smith & Rios, 2018). Most of the Paraguayan Chaco (a convergence of Pantanal, Cerrado, Dry and Humid Chaco ecoregions) is located within the area of the M. tridactyla geographic distribution, however, our study area is located a few kilometers from the possibly extinct zone towards the southern limit (Miranda et al, 2014a).…”
mentioning
confidence: 99%
“…The area surrounding the EOO is severely affected by extensive commercial plantations and urban settlements, with only c. 50% of the ecoregion unaffected (Armenteras et al, 2003; Sánchez-Cuervo et al, 2012; Angulo et al, 2019). This limits connectivity (Bright, 1993), which is important for the persistence of a species (Passos et al, 2016). Maintenance, extension or connection of protected areas, connecting the relict habitats, could help to protect C. vestitus (Cofré & Marquet, 1999; Amori & Gippoliti, 2003; Armenteras et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The giant anteater ( Myrmecophaga tridactyla ) is the largest of the Neotropical vermilinguans and the largest representative of the family Myrmecophaga (Gaudin et al, 2018; Medri et al, 2006; Smith, 2007) and has presented a wide geographical distribution, occurring from northern Central America to southern South America (Passos et al, 2017; Smith, 2007). These species are myrmecophagous since their diet consists basically of ants and termites (Naples, 1999).…”
Section: Introductionmentioning
confidence: 99%